Increased CD39 nucleotidase activity on microparticles from patients with idiopathic pulmonary arterial hypertension. - Scott H Visovatti (PLoS ONE, 2012)
BACKGROUND:Idiopathic pulmonary arterial hypertension (IPAH) is a devastating disease characterized by increased pulmonary vascular resistance, smooth muscle and endothelial cell proliferation, perivascular inflammatory infiltrates, and in situ thrombosis. Circulating intravascular ATP, ADP, AMP and adenosine activate purinergic cell signaling pathways and appear to induce many of the same pathologic processes that underlie IPAH. Extracellular dephosphorylation of ATP to ADP and AMP occurs primarily via CD39 (ENTPD1), an ectonucleotidase found on the surface of leukocytes, platelets, and endothelial cells. Microparticles are micron-sized phospholipid vesicles formed from the membranes of platelets and endothelial cells. OBJECTIVES:Studies here examine whether CD39 is an important microparticle surface nucleotidase, and whether patients with IPAH have altered microparticle-bound CD39 activity that may contribute to the pathophysiology of the disease. METHODOLOGY/PRINCIPAL FINDINGS:Kinetic parameters, inhibitor blocking experiments, and immunogold labeling with electron microscopy support the role of CD39 as a major nucleotidase on the surface of microparticles. Comparison of microparticle surface CD39 expression and nucleotidase activity in 10 patients with advanced IPAH and 10 healthy controls using flow cytometry and thin layer chromatograph demonstrate the following: 1) circulating platelet (CD39(+)CD31(+)CD42b(+)) and endothelial (CD39(+)CD31(+)CD42b(-)) microparticle subpopulations in patients with IPAH show increased CD39 expression; 2) microparticle ATPase and ADPase activity in patients with IPAH is increased. CONCLUSIONS/SIGNIFICANCE:We demonstrate for the first time increased CD39 expression and function on circulating microparticles in patients with IPAH. Further research is needed to elucidate whether these findings identify an important trigger for the development of the disease, or reflect a physiologic response to IPAH.